Wine routes in theory and practice of the development of religious and wine tourism of Serbia: A case study of Fruška Gora - Penjišević Ivana; Milosavljević Saša; Burić Dragan (Zbornik Radova: Geografski Fakultet Univerziteta u Beogradu, 2023)
In the last two decades, wine tourism has become increasingly important in the development plans for tourism in the Republic of Serbia, especially considering that it is very profitable. Among the key subjects of wine tourism, wine producers in the regions of Srem, Aleksandrovačka Župa and Šumadija stand out. The tourist products also become recognizable products of the wine-growing regions, as the wineries have tasting rooms where wine and homemade food are combined for visitors. In this way, the identity of the geographic region is defined through the promotion of wine. Before the outbreak of the pandemic, several hundred busses came every year to the wineries in the above-mentioned regions of Serbia, so that almost 40% of the wine production was sold practically on the doorstep during weekends and holidays. The work analyzes in particular the wine roads of Fruška Gora, which have always had great potential and an important role in Serbian viticulture. The research focused on the complementarity of wine and religious tourism, with special attention to the production of monastery wines in own economy.